Behavioral Factors Influencing Peer-to-Peer Lending Usage: A Systematic Literature Review from the Perspective of Indonesian Borrowers' Needs - Febriana, Mazaya (LP2M IAIN Palopo, 2025)
This systematic literature review (SLR) investigates behavioral factors affecting peer-to-peer (P2P) lending adoption from Indonesian borrowers' financial needs viewpoint. Utilizing a descriptive qualitative approach with PRISMA guidelines, literature was retrieved through Publish or Perish with keywords